MRI-defined T3, clear mesorectal fascia mid-low rectal cancer: is neoadjuvant treatment necessary? - Zeng, Ziwei; Li, Ze; Luo, Shuangling; Huang, Liang; Liang, Zhenxing; Zheng, Xiaobin; Li, Wenxin; Xiong, Li; Liu, Huashan; Kang, Liang (Journal of gastroenterology and hepatology, 2024)
Aim: Neoadjuvant treatments (nCRT) are becoming the standard treatment for patients with stage II or III mid-low rectal cancer. Recently, some studies have shown that surgery alone may be sufficient for patients with T3 rectal cancer. This raises the question of whether nCRT is necessary for all patients with T3 rectal cancer. Therefore, this study compared the clinical outcomes of patients with MRI-defined T3, clear MRF mid-low rectal cancer treated with surgery alone (TME group) or nCRT followed by surgery (nCRT + TME group). Methods: A total of 1509 patients were enrolled in this study. After a 1:1 propensity score matching analysis, 480 patients were included in each group. The primary endpoint was 3-year disease-free survival (DFS). The secondary endpoints included the perioperative outcomes, histopathologic outcomes, and other follow-up outcomes. Results: nCRT had advantages in rates of sphincter-preserving surgery and tumor downstaging, but it was accompanied by a higher rate of enterostomies. At 3 years after surgery, local recurrence occurred in 3.3% of patients in the TME group and in 3.5% of patients in the nCRT + TME group (P = 0.914), the DFS rates were 78.3% in the TME group and 75.3% in the nCRT + TME group (P = 0.188), and the overall survival rates were 90.3% in the TME group and 89.9% in the nCRT + TME group (P = 0.776). Conclusions: Surgery alone versus nCRT followed by surgery may provide similar long-term oncological outcomes for patients with MRI-defined T3, clear MRF, and mid-low rectal cancer. nCRT may cause overtreatment in some patients.
Gesehen am 22.02.2024